ANALYSIS OF FACTORS AFFECTING USERS’ ATTITUDE TOWARD THE YOUTUBE ADS AND THEIR EFFECTS ON PURCHASE INTENTION - Shifa Nabila; Adrian Achyar (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2019)
ABSTRACTResearch Purposes – This study aims to identify five factors in YouTube advertising (entertainment, informativeness, customization, irritation and credibility) which might effect on ad value, and attitude toward YouTube ads, leading to purchase intention of consumers.Methods – The study uses conceptual models where their hypothesis is that the ad value is positively correlated with respect to the attitude toward YouTube ads, which then affects consumer’s purchase intention.Result – This study found that entertainment, customization, and credibility is positively effected to advertising value on YouTube, where ad value has a positive effect on attitude toward YouTube ads and purchase intention of consumer.Research limitations – For this study, our respondents include 248 active YouTube users in Indonesia that will be used for data collection and analysis.Originality/value – In addition, this study found that irritation is negatively effected to advertising advertising value on YouTube, and informativeness has no effect on advertising value on YouTube.Keywords: Ad value, attitude toward YouTube ads, credibility, customization, entertainment, informativeness, irritation, purchase intention.